2016
DOI: 10.14260/jemds/2016/1650
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Diabetic and Reno-Protective Effect of the Ethanolic Extract of Solanum Indicum in Alloxan-Induced Diabetic Rats

Abstract: BACKGROUNDThe objective of the present study was to investigate the anti-diabetic and renoprotective activity of Solanum indicum in alloxaninduced diabetic rat. MATERIALS AND METHODSEthanolic extract of Solanum indicum was administered orally at a dose of 100 mg/kg. Blood glucose levels were measured by glucose oxidase method on weekly intervals for 4 weeks. Urine samples were collected before the induction of diabetes and at the end of 8 weeks of treatments and analysed for urine volume, urinary protein and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Essentially, bioactive compounds of some of the investigated plants in this study have produced antidiabetic effects by acting on specific targets (For example, agonists of PPARγ such as Citrus sinensis (L.) Osbeck) [124], while other researchers only reported antidiabetic activities without definite pharmaceutical targets [144,145]. For successful drug development, it is pivotal to identify and select targets of therapeutic compounds.…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 98%
“…Essentially, bioactive compounds of some of the investigated plants in this study have produced antidiabetic effects by acting on specific targets (For example, agonists of PPARγ such as Citrus sinensis (L.) Osbeck) [124], while other researchers only reported antidiabetic activities without definite pharmaceutical targets [144,145]. For successful drug development, it is pivotal to identify and select targets of therapeutic compounds.…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 98%
“…Hence, α-amylase and α-glucosidase inhibitors slow the digestion of starch in the small intestine, which decreases the amount of glucose entering the bloodstream leading to an improved insulin response [ 138 ]. Previous studies reported the hypoglycemic effects of SILF [ 139 ] and S. melongena [ 140 ], and these may have been mediated through inhibiting the α-amylase and α-glucosidase, due to the presence of phenolic compounds. The TPC in SALF (mg GAE/g DW) is substantially higher than in SILF [ 120 ], suggesting inhibiting properties of SALF regarding α-amylase and α-glucosidase activity, which may be mediated by tannins as similar effects have been reported for tannin-containing Terminalia chebula Retz [ 141 ].…”
Section: Solanum Anguivi Lam Fruit’s Antidiabementioning
confidence: 99%